Poverty Dynamics In Ghana: Evidence From Monetary And Non-Monetary Poverty - Arthur, S. (University of Ghana, 2021)
ABSTRACT Poverty and the fight to overcome it is far from over in Sub-Saharan Africa where more than half of the world’s poor is found. Even though Ghana has made great strides in combating the problem of poverty, the battle is yet to be won in the country given the multidimensional nature of the problem. This study analysed poverty dynamics in Ghana using both monetary and nonmonetary measures of poverty for the period 2009 to 2014. Using a panel of 4,366 household heads interviewed in the first two-waves of the Ghana National Socioeconomic Survey database, the study draws a distinction between chronic and transient poverty using both monetary and non-monetary measures and assessed the relationships that exist between the two phenomena. The results showed that whereas the chronic monetary poor for the period stood at 9.3 per cent, the chronic non-monetary poor for the data ranged between 74 per cent and 1.6 per cent for different non-monetary variables. Using a multinomial logit regression, the study discovered that the dynamics of poverty are driven by household demographic characteristics, human capital, economic, geographic and asset-related factors. The results revealed the different magnitude of factors underpinning the movement in and out of poverty are different for transient and chronic poverty in Ghana. The results of the monetary poverty measures were also compared with the results of non-monetary poverty measures and showed that monetary poverty does not exactly predict all the various aspects of non-monetary poverty and depending on the number of deprivations a household suffers from, different factors determine the deprivations. The study recommended separate policies to fight monetary poverty and nonmonetary poverty. The study further, recommended that four of the non-monetary poverty deprivations, children’s nutritional status, adults’ nutritional status, adults’ schooling and sanitation should be given more attention as they showed an upward trend in the study period. Again, realizing that the determinants of chronic and transient poverty were different, the study recommended different and appropriate short and long-term policies to deal with each.
PhD. Development Studies
Keywords: Poverty Dynamics In Ghana; Monetary; Non-Monetary; Evidence